2017
DOI: 10.1063/1.4985593
|View full text |Cite
|
Sign up to set email alerts
|

Shock initiation of explosives: High temperature hot spots explained

Abstract: We investigated the shock initiation of energetic materials with a tabletop apparatus that uses km s−1 laser-driven flyer plates to initiate tiny explosive charges and obtains complete temperature histories with a high dynamic range. By comparing various microstructured formulations, including a pentaerythritol tetranitrate (PETN) based plastic explosive (PBX) denoted XTX-8003, we determined that micron-scale pores were needed to create high hot spot temperatures. In charges where micropores (i.e., micron-size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 32 publications
7
33
0
Order By: Relevance
“…Recently, simulations of PETN and RDX which include chemical reaction have observed hot spot temperatures on the order of ∼4000 K for collapsing pores which are 10–100 nm in diameter . These temperatures are consistent with those our group observed recently in PBX systems based on PETN . As reported previously, the hot spot temperatures were observed concurrent with impact without a measurable temperature rise time, indicating the local temperatures under shock compression reached 4000 K in <4 ns, which corresponds to a heating rate of >10 12 K/s.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Recently, simulations of PETN and RDX which include chemical reaction have observed hot spot temperatures on the order of ∼4000 K for collapsing pores which are 10–100 nm in diameter . These temperatures are consistent with those our group observed recently in PBX systems based on PETN . As reported previously, the hot spot temperatures were observed concurrent with impact without a measurable temperature rise time, indicating the local temperatures under shock compression reached 4000 K in <4 ns, which corresponds to a heating rate of >10 12 K/s.…”
Section: Introductionsupporting
confidence: 90%
“…Representative 2D tomogram slices of RDX‐ and TNT‐based PBXs are shown in Figure b–c. Computer tomography with 1 μm pixel resolution did not show void spaces in X‐PETN, or X‐RDX suggesting that samples have, at most, sub‐micron void spaces similar to prior work . X‐TNT and X‐TATB tomograms showed larger crystals and occasional void space consistent with their lower observed density.…”
Section: Methodssupporting
confidence: 75%
“…In Figure we see a crystal with an internal void, we see the brief flare caused by gas compression in the void, and subsequently, we see a deflagration moving through the explosive. Previously, we showed that in large voids hot spots reach temperatures >6000 K due to the compression of produced gasses within the voids as the shock propagates across the needs . From this, it is reasonable to expect that the central hot spot carries little thermal mass and does not heat the single‐crystal enough on thermalization to ignite on its own.…”
Section: Discussionmentioning
confidence: 99%
“…In the past several years, multiple research groups have developed tabletop shock generation systems to facilitate a greater understanding of the many facets of the complex phenomena involved in topics ranging from detonation propagation , to chemical reaction pathways under shock conditions , and hot spot temperature measurements . With the exception of the work of Tappan et al .…”
Section: Introductionmentioning
confidence: 99%
“…A well-calibrated material model and equation of state might possibly capture all of the different mechanisms; unfortunately, such models are limited by the available thermophysical property data relevant to the high rates of deformation (> 10 4 s −1 ) and high pressures (> 1 GPa) associated with pore collapse. Experimental observations of pore collapse have progressed over the years to include high speed imaging 19 , particle image velocimetry 20 , and ultrafast spectroscopy techniques 21,23 . From these studies, there exist data on the pore collapse time, free surface velocity, and shock viscosity, which are useful for informing the different hot spot mechanisms and for calibrating the material models.…”
Section: Introductionmentioning
confidence: 99%